Examining the legality of Rahn contracts in Malaysian Islamic financial institutions = Meneliti kesahihahn akad Rahnu di institutusi kewangan Islam - Zakariyah, Luqman; Musah, Mohammed Kabiru (IIUM Press, International Islamic University Malaysia, 2018)
This study aims to investigate the legality of rahn contracts in Malaysian Islamic Financial Institutions. Specifically, it attempts to examine how rahn is used in these institutions as well as the Shariah issues related to it so as to ascertain the extent to which it has achieved the objectives for which it was legislated by the Shariah. To achieve these objectives, inductive method is used to gather information on rahn both from classical and modern books of Islamic Jurisprudence. Qualitative approach with interview as the instrument of data collection was also adopted to elicit data from the following Malaysian Islamic Financial Institutions: Bank Rajhi, Maybank, Bank Muamalat and Bank Islam. This research concludes that the rahn used in these Islamic financial institutions has achieved the objectives for which it was legislated. It is also used through several combinations of contracts such as wadiah yad dhamanah (savings with a protection guarantee), ujrah (fee), qard hasan (loan) among others. However, some transactions in which the rahn appears need to be reviewed, and amended to comply with the provisions of Islamic Shariah. ********************************************************** Kajian ini bertujuan meneliti kesahihan Akad al-Rahnu di Institusi Kewangan Islam di Malaysia. Secara khususnya, kajian ini cuba meneliti aplikasi al-Rahnu di institusi-institusi kewangan Islam Malaysia serta isu-isu Shariah yang berkaitan dengannya, demi memastikan akad tersebut mecapai objektif yang digariskan oleh Shariah. Demi mencapai objektif tersebut, metod induktif telah digunakan untuk mengumpul maklumat daripada buku-buku Fiqh klasik dan kontemporari. Pendekatan kualitatif dengan wawancara sebagai instrumen pengumpulan data juga diguna pakai untuk mendapatkan data dari Institusi Kewangan Islam Malaysia berikut: Bank Rajhi, Maybank, Bank Muamalat dan Bank Islam. Kajian ini menyimpulkan bahawa akad rahnu yang digunakan dalam institusi kewangan Islam ini telah mencapai objektif sebagaimana ditetapkan oleh Shariah. Ia juga digunakan melalui beberapa kombinasi kontrak seperti wadiah yad dhamanah (simpanan dengan jaminan perlindungan), ujrah (fee), qard hasan (pinjaman) dan lain-lain. Walau bagaimanapun, beberapa transaksi yang melibatkan rahnu perlu dikaji semula, dan dipinda supaya selari dengan Syariah.